Label-free on chip quality assessment of cellular blood products using real-time deformability cytometry. Issue 13 (27th May 2020) - Aurich, Konstanze; Fregin, Bob; Palankar, Raghavendra; Wesche, Jan; Hartwich, Oliver; Biedenweg, Doreen; Nguyen, Thi-Huong; Greinacher, Andreas; Otto, Oliver
Abstract : Real-time deformability cytometry is a unique tool for quality assessment of therapeutic blood cells utilizing their mechanical properties. Abstract : Without cellular blood products such as platelet concentrates (PC), red blood cell concentrates (RCC), and hematopoietic stem cells (HPSC) modern treatments in medicine would not be possible. An unresolved challenge is the assessment of their quality with minimal cell manipulation. Minor changes in production, storage conditions, or blood bag composition may impact cell function, which can have important consequences on product integrity. This is especially relevant for personalized medicine, such as autologous T-cell therapy. Today a robust methodology that globally determines cell status directly before transfusion or transplantation is lacking. We demonstrate that measuring viscoelastic characteristics of peripheral blood cells using real-time deformability cytometry (RT-DC) provides comprehensive information on product quality, which is not accessible using conventional quality control tests. In addition, RT-DC requires few cells, a minimal sample volume and has a rapid turnaround time. We compared RT-DC to standard in vitro quality assays assessing: i) PC after storage at 4 °C and room temperature; ii) magnetic nanoparticle labeled platelets; iii) RCC stored in blood bags with different plasticizers; iv) RCC after gamma irradiation; and v) HPSC after cryopreservation with 5% or 10% dimethyl sulfoxide, respectively. Additionally, we evaluated the engraftment time of patients' platelets and leukocytes after transplantation of HPSC products. Our results demonstrate that label-free mechano-phenotyping can be used as a potential biomarker for quality assessment of cell-based pharmaceutical products.